A linguagem de crianças com a Síndrome Congênita do Zika Vírus um guia para pais - Verdu, Ana Cláudia Moreira Almeida (Editora Oficina Universitária, 2021)
This guide provides information for parents and other family members of children with Congenital Zika Virus Syndrome. It presents information about simple everyday attitudes that can stimulate the language of these children. It is understood that this guide will not solve all the communication problems of this population, nor will it replace therapies (speech therapy, psychological, among others), but it will be able to minimize the damage in communication due to Congenital Zika Virus Syndrome, it will help to identify small achievements and, still, value each advance, no matter how small it may seem. It is always important to remember: speaking is a very complex skill for some children.